2018
DOI: 10.1056/nejmoa1807119
|View full text |Cite
|
Sign up to set email alerts
|

VX-659–Tezacaftor–Ivacaftor in Patients with Cystic Fibrosis and One or Two Phe508del Alleles

Abstract: BACKGROUND The next-generation cystic fibrosis transmembrane conductance regulator (CFTR) corrector VX-659, in triple combination with tezacaftor and ivacaftor (VX-659-tezacaftor-ivacaftor), was developed to restore the function of Phe508del CFTR protein in patients with cystic fibrosis. METHODS We evaluated the effects of VX-659-tezacaftor-ivacaftor on the processing, trafficking, and function of Phe508del CFTR protein using human bronchial epithelial cells. A range of oral VX-659-tezacaftor-ivacaftor doses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
274
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 284 publications
(282 citation statements)
references
References 20 publications
7
274
0
1
Order By: Relevance
“…The 2018 guidelines for the use of CFTR modulator therapy made a strong recommendation for the use of ivacaftor/lumacaftor in patients homozygous for Phe508del and with a forced expiratory volume in 1 second (FEV 1 ) <90% predicted . In October 2018, 2 breakthrough studies involving a triple combination of CFTR modulators were published . Both studies demonstrated improvement over the predicted percentage for FEV 1 , above what was already achieved by dual therapy in patients homozygous for Phe508del and with a Phe508del‐MF mutation.…”
Section: Cf‐associated Liver Diseasementioning
confidence: 99%
“…The 2018 guidelines for the use of CFTR modulator therapy made a strong recommendation for the use of ivacaftor/lumacaftor in patients homozygous for Phe508del and with a forced expiratory volume in 1 second (FEV 1 ) <90% predicted . In October 2018, 2 breakthrough studies involving a triple combination of CFTR modulators were published . Both studies demonstrated improvement over the predicted percentage for FEV 1 , above what was already achieved by dual therapy in patients homozygous for Phe508del and with a Phe508del‐MF mutation.…”
Section: Cf‐associated Liver Diseasementioning
confidence: 99%
“…Although the current available combinations of potentiator (ivacaftor) and corrector (lumacaftor or tezacaftor) have provided some, albeit modest, improvement in lung function, individuals with Phe508del mutations remain a challenge. Among those who have at least one such mutation, approximately half are homozygous and approximately one‐third have a minimal function (MF) CFTR mutation as the second allele . MF mutations either produce no CFTR or a protein that is not responsive to CFTR modulators.…”
Section: Cftr Modulator Therapymentioning
confidence: 99%
“…The initial results of two small studies using the triple CFTR approach are now available . Both studies were conducted in adults who were either Phe508del homozygous or heterozygous for the Phe508del and an MF mutation, and were already receiving dual therapy with ivacaftor and tezacaftor.…”
Section: Cftr Modulator Therapymentioning
confidence: 99%
“…Triple drug combinations that improve the activity of the cystic fibrosis transmembrane conductance regulator (CFTR), the anion channel that is defective or deficient in the condition, significantly improve lung function in patients with cystic fibrosis who have the most common CFTR gene mutations, two early stage randomised trials have reported 12…”
mentioning
confidence: 99%
“…The results, reported in the New England Journal of Medicine ,12 showed that patients treated with the VX-659-combination showed significant increases in the percentage of predicted forced expiratory volume in one second (FEV 1 ) at day 29. At the highest dose, FEV 1 increased by an average of 13.3% ± standard error 1.9% (95% confidence interval 9.5% to 17.1%; P<0.001), compared with no change in the placebo group.…”
mentioning
confidence: 99%